DOES ECONOMIC LIBERTY BOLSTER ECONOMIC PERFORMANCE? - Naape, Baneng (Universitas Nasional, 2024)
Institutional quality and economic liberty have emerged as key determinants of economic growth and development. This study investigates the relationship between economic liberty and economic growth in the Southern African Development Community (SADC) region. Utilizing a dynamic system generalized method of moments (GMM) and Granger causality analysis, the research reveals a positive and significant relationship between components of economic liberty and economic growth. The findings also indicate that economic liberty and economic growth are interdependent, suggesting that they are jointly determined. These results underscore the importance of deepening regional integration among SADC member states through increased intra-regional trade, financial integration, and the implementation of infrastructure projects to lower business costs.